Sur les certaines couples T des complexes de droites stratifiables à l’aide des éléments linéaire - Vaškas, P. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Вашкас. О некоторых парах Т комплексов прямых, расслояемых посредством линейных элементовP. Vaškas: Apie kai kuriuos tiesių kompleksų dvejetus T, išsluoksniuojamus su tiesinių elementų pagalba